2015
DOI: 10.1080/14786419.2015.1046130
|View full text |Cite
|
Sign up to set email alerts
|

A new phenolic compound with antioxidant activity from the branches and leaves of Pyrus pashia

Abstract: The branches and leaves of Pyrus pashia are used to cure abdominal pain and diarrhoea in Chinese folk medicine. A new phenilic compound, 4-O-β-d-glucopyranosylbenzyl-benzoate ester (1), along with 21 known ones (2-22) were isolated from the branches and leaves of this plant. Compounds 2 and 3 displayed remarkable antioxidant activities against 1,1-diphenyl-2-picrylhydrazyl radical (IC50 = 13.26 ± 0.04 μM, 13.28 ± 0.11 μM, respectively), which were at the same grade as positive control rutin. The caffeoyl group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Thus, chemical structure of 3 was elucidated as 3 ‐O‐β‐ D‐glucopyranosyl‐1‐(3′,5′‐dimethoxy‐4‐hydroxyphenyl‐1‐propanone). [ 5 ] This was the first isolation of 3 from the Elsholtzia genus.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, chemical structure of 3 was elucidated as 3 ‐O‐β‐ D‐glucopyranosyl‐1‐(3′,5′‐dimethoxy‐4‐hydroxyphenyl‐1‐propanone). [ 5 ] This was the first isolation of 3 from the Elsholtzia genus.…”
Section: Resultsmentioning
confidence: 99%
“…The high antiproliferative activity may be due to high phenolic and flavonoid content and ellagic content (47). Li et al (37) also demonstrated the cytotoxicity of terpenoids (36,37). The aforementioned studies indicate that P. pashia extract has various traditional uses, such as in the treatment of typhoid fever, pain relief and cough, as well as for the treatment of other inflammatory diseases.…”
Section: Anti-inflammatory and Antiproliferative Activitiesmentioning
confidence: 97%
“…A previous study demonstrated the total phenolics and the free radical scavenging level of methanol and water extracts of leaves; the methanolic leaf extract was shown to have the highest phenolic content (351.16±0.43 mg/g extract) (8). Li et al (37) also demonstrated that the butanol extract of the bark and leaves possessed a high antioxidant level. Overall, the aforementioned studies highlighted the antioxidants level of various plant parts of P. pashia and broadened their applications to prevent degenerative diseases.…”
Section: Phytochemistry and Pharmacological Propertiesmentioning
confidence: 98%
See 2 more Smart Citations